A cross-sectional study to find the prevalence of hyperprolactinemia in infertile euthyroid patients in a hospital - Badesara, Sanjay; Jakhar, Kiran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Infertility whether primary or secondary, has multi-factorial causation, out of which hormonal imbalance is one of the important factors. Current study evaluates the prevalence of hyperprolactinemia in infertile euthyroid women. Methods: After Ethics Committee approval and written informed consent, all infertile euthyroid women (n=153) with age group 20-40 years attending outpatient department of general hospital, with marriage duration of at least one year and willing to participate in study were recruited. Male factor infertility, women with diagnosed hyperprolactinemia, thyroid abnormality, tubal factors, any congenital anomaly of urogenital tract or obvious organic lesion or with history of anxiety or other psychological disorders and on treatment for same were excluded. Detailed obstetrics history with relevant laboratory, radiological investigations including serum prolactin level was done. Results: Mean serum prolactin level was 13.89±10.03 ng/ml. Out of 153 participants, 13 had hyperprolactinemia which comprised 8.50% of the sample. The mean of the level of serum prolactin level in primary infertility cases was 13.18±8.485 ng/ml while that in secondary infertility was 17.21±15.1 ng/ml. Primary infertility was approximately half (53.85%) in hyperprolactinemia group and majority (85%) in normoprolactinemia group. Duration of married life, infertility and fasting blood sugar were positively correlated with prolactin levels. Conclusions: Prevalence of hyperprolactinemia was 8.50% with higher serum prolactin level in secondary infertility as compared to primary infertility. So, estimation of serum prolactin levels in infertile patients with euthyroid status can help to a large extent in finding the cause of infertility and may help in further management.